What determines the export performance? A comparative analysis at the world level - Crespo, Nuno (2011)
We use constant market share (CMS) analysis to measure the variations in the market share of 82 of the world’s principal exporting countries between 1995/97 and 2005/07. The results of this analysis serve to stress the importance of competitiveness in explaining export performance. Furthermore, the existence is observed of a spatial tendency, reflected in the fact that countries that are geographically close to each other tend to display a similar behavior with regard to market share evolution and the components into which the variation is broken down.